2020
DOI: 10.1017/s0003055420000416
|View full text |Cite
|
Sign up to set email alerts
|

Seniority-Based Nominations and Political Careers

Abstract: This paper investigates party use of seniority systems to allocate nominations for elected and appointed offices. Such systems, which can regulate party members’ access to offices at multiple levels of their careers, are defined by two main rules or norms: an incumbent re-nomination norm and a seniority progression norm. Using comprehensive electoral and candidate data from Norwegian local and national elections from 1945 to 2019, we find systematic patterns consistent with these two norms. Our work illuminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 59 publications
6
57
2
Order By: Relevance
“…Finally, our results on the effects of rankings on party decisions between rounds contribute to a rich literature exploring the properties of two-round voting systems (e.g., Osborne and Slivinski, 1996;Piketty, 2000;Bouton, 2013;Bordignon et al, 2016;Bouton et al, 2019;Cipullo, 2019), and they echo recent work showing that parties tend to promote candidates ranked higher by voters in open-list elections (Folke et al, 2016;Meriläinen and Tukiainen, 2016;Cirone et al, 2020), that their likelihood to appoint a government increases when they receive more seats or votes (Fujiwara and Sanz, 2020), and that incumbents elected with a higher rank in multi-member districts are more likely to win higher office in future elections (Dulay and Go, 2021).…”
Section: Contribution To the Literaturesupporting
confidence: 80%
“…Finally, our results on the effects of rankings on party decisions between rounds contribute to a rich literature exploring the properties of two-round voting systems (e.g., Osborne and Slivinski, 1996;Piketty, 2000;Bouton, 2013;Bordignon et al, 2016;Bouton et al, 2019;Cipullo, 2019), and they echo recent work showing that parties tend to promote candidates ranked higher by voters in open-list elections (Folke et al, 2016;Meriläinen and Tukiainen, 2016;Cirone et al, 2020), that their likelihood to appoint a government increases when they receive more seats or votes (Fujiwara and Sanz, 2020), and that incumbents elected with a higher rank in multi-member districts are more likely to win higher office in future elections (Dulay and Go, 2021).…”
Section: Contribution To the Literaturesupporting
confidence: 80%
“…These findings add new insights to the extensive literature on incumbency effects, and they are also closely related to work on seniority-based nomination norms in politics (McKelvey and Riezman 1992;Epstein et al 1997;Cirone, Cox, and Fiva 2020).…”
supporting
confidence: 60%
“…Researchers in the past have found that work experience is positively associated with career/job promotions (Cirone et al, 2021;Ng et al, 2005;Metz and Tharenou, 2001;Rasdi et al, 2011). Rasdi et al (2011) investigated a wide range of factors in predicting job promotions among Malaysian employees and found that having longer work tenure was positively related to high promotions and pay.…”
Section: Work Experiencementioning
confidence: 99%